Radiographic changes in delayed white cord syndrome from postsurgical cervical myelopathy: A case report and review of the literature - Serena Sheen; Volney Sheen (Radiology Case Reports)
White cord syndrome (WCS), also referred to as reperfusion injury of the spinal cord, is a rare condition involving sudden neurological deterioration following cervical spinal decompression. The syndrome is diagnosed in the absence of an iatrogenic cord injury or perioperative complications. Both loss of neurophysiological signaling during intraoperative monitoring and the appearance of hyper-intensity on T2-weighted magnetic resonance imaging are hallmarks of WCS. We present a report of a female patient who presented with the condition and followed her imaging studies longitudinally. Imaging studies showed prolonged and persistent contrast enhancement over a year and a half postsurgery. Such findings have not previously been reported with WCS. We provide a brief review of the literature, highlighting the main radiologic findings.